2002
DOI: 10.3758/bf03195791
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic effects of the Ebbinghaus illusion in grasping: Support for a planning/control model of action

Abstract: The distinctionbetween the premovement planning of an action and its on-line control has a long history (e.g., Jeannerod, 1988;Keele & Posner, 1968;Woodworth, 1899). Here, we demonstrate that the earlier portions of a grasping movement are more affected by the Ebbinghaus illusion than are the latter portions. These results provide further support for a planning/control model (Glover, 2001;Glover & Dixon, 2001a, 2001b, 2001d in which planning is more susceptible to illusions than control. The results do not sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
168
9
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(192 citation statements)
references
References 68 publications
(148 reference statements)
14
168
9
1
Order By: Relevance
“…Usually (but not always) this will result in an underestimation of the variability for the corrected illusion effects (and, consequently, in liberal statistical tests). Unfortunately, this problem is present in the study of Glover and Dixon (2002). As an example, we calculated the corrected illusion effects in the same way as Glover and Dixon (2002) did.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually (but not always) this will result in an underestimation of the variability for the corrected illusion effects (and, consequently, in liberal statistical tests). Unfortunately, this problem is present in the study of Glover and Dixon (2002). As an example, we calculated the corrected illusion effects in the same way as Glover and Dixon (2002) did.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this problem is present in the study of Glover and Dixon (2002). As an example, we calculated the corrected illusion effects in the same way as Glover and Dixon (2002) did. This results in corrected illusion effects of: 1.32 ± 0.34 for t = 100%, 1.23 ± 0.34 for t = 75%, 1.27 ± 0.37 for t = 50%, 1.14 ± 0.78 for t = 25%, and 21.51 ± 11.44 for t = 0%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One could wonder, moreover, what would be the benefit for the visual system of having two independent pathways dealing with identical spatial processing. This also rules out the possibility that context information influenced motor planning but not control process, allowing on-line minimization of the spatial error of the movement (the planning-control model; Glover, 2004;Glover & Dixon, 2002). An alternative would be to consider that the processing of context information remains the prerogative of the ventral stream, which can influence the sensorimotor system in some circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…One of the pieces of behavioural evidence for the PCM was a careful examination of the unfolding movement during actions towards visual illusions. Glover and Dixon [13] showed that the effect of an illusion on grip aperture was stronger at the start of the movement and diminished as the movement progressed, potentially indicating that movement planning and movement control were drawing upon different representations of the target and its environment.…”
Section: Cortical Substrates For Visuomotor Processingmentioning
confidence: 99%